Rancang Bangun Control Valve untuk Sistem Pengendalian pada Tangki Peyimpanan - Azhim, Fadlul; Gayuh Prasetya, Hendrik Elvian; Tridianto, Erik (Fakultas Teknik Universitas Tribhuwana Tunggadewi, 2019)
The control system is an engineering discipline that involves mechanisms and algorithms to control the output of a process with the desired results. Modern industries and power plants use control valves as a control system in storage tanks. The control valve is a very important component in this regard as a final element. Therefore, we designed a control valve starting from the sizing control valve, mathematical modeling of the system to programming on Arduino and Visual Basic .NET so that it can be observed and understood directly. After sizing the control valve, it can be seen the type of valve that meets the valve opening standard is Globe valve at 46.8% and Ball valve at 33.0%. In this study, the commonly used PID tuning method is Ziegler Nichols tuning method to test the control system. The PID parameter is obtained through the tuning results in the Matlab simulation using mathematical modeling of the system. Control valve simulation with Matlab produces parameters Kp= 0.5625, Ti= 0.3, and Td= 0.7. While the control level produces a parameter Kp= 1.36, Ti= 3.33. The control level of the storage tank is better to use PI control compared to PID controls which continue to increase water levels. Changes in set point from 1 cm to 20 cm produce a 37-seconds settling time with a maximum overshoot value of 6 cm.